1986
DOI: 10.1161/01.atv.6.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Improved arterial distensibility in normotensive subjects on a low salt diet.

Abstract: Arterial pulse wave velocity (PWV), a noninvasive index of arterial distensibility, was measured in 57 normotensive subjects who followed a voluntary low salt diet for a period ranging from 8 months to 5 years (mean, 24.8 months). Subjects who followed a regular diet were matched for age and mean arterial pressure with the low salt (LS) sample and were used as controls (C). For both samples, subjects were divided into three age groups: Group 1 (aged 2 to 19 years, n = 16), Group 2 (29 to 44 years, n = 26), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
2
13

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(142 citation statements)
references
References 17 publications
2
125
2
13
Order By: Relevance
“…28 Inhibition of angiotensin-converting enzyme has been shown to reduce arterial stiffness, 29 as has a low-salt diet. 30 Additionally, we have previously shown in this same population a strong relationship between obesity and larger arterial diameters and wall thickening. 31 Dilation and wall thickening may predispose the arteries of obese individuals to more rapid arterial stiffening.…”
Section: Discussionmentioning
confidence: 59%
“…28 Inhibition of angiotensin-converting enzyme has been shown to reduce arterial stiffness, 29 as has a low-salt diet. 30 Additionally, we have previously shown in this same population a strong relationship between obesity and larger arterial diameters and wall thickening. 31 Dilation and wall thickening may predispose the arteries of obese individuals to more rapid arterial stiffening.…”
Section: Discussionmentioning
confidence: 59%
“…The studies of Avolio et al 9 - 27 have suggested that people with a low sodium intake may have less stiff aortas than those consuming salt in higher amounts.,In our study, the association of aortic stiffness with salt intake was more complex because the regression was modified by the level of blood pressure. As Fig 3 shows, the association of aortic elastic modulus with habitual sodium intake was strongly positive in people with low mean blood pressure but faded away in people with blood pressure that was higher but still within the normotensive range.…”
Section: Potential Predictors Of Aortic Elastic Modulusmentioning
confidence: 99%
“…Prior small scale intervention studies of effects of dietary sodium restriction shows that salt intake is associated with arterial stiffness 16,22 and the study done by Stewart et al 23 shows that acute reduction of blood pressure by nitroglycerin normalizes large artery stiffness in normortensives but does not normalize that in essential hypertension, suggesting that the latter group requires long-term intervention to change arterial stiffness. Studies of pharmacological blood pressure lowering interventions have also shown the similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…Salt substitutes with reduced sodium and increased potassium substantially lower blood pressure. [13][14][15] There are some limited data to suggest that long-term consumption of a diet low in salt may reduce arterial stiffness independent of blood pressure reduction 16 although data from high-risk individuals with existing vascular disease are few. There are also data showing positive correlations of sodium intake 17 and negative correlations of potassium intake 18 with arterial stiffness providing a strong rationale for beneficial effects of salt substitution beyond blood pressure lowering although once again data about effects in high-risk individuals are limited.…”
Section: Introductionmentioning
confidence: 99%